Electrospun Nylon 6 Nanofibre Water Filtration Media For Wastewater Treatment - Roslan, Nur Saidatul Akmal (2019)
Uncontrolled discharge of wastewater effluent has been a major concern due to the negative impact to human health and the environment. The issue becomes even more serious if the location of discharge point is located upstream of the river flow. Recently, increasingly stringent regulation has caused filter manufacturers to explore new materials to improve their products. Water filtration media using ultrafine fibres have attracted much attention among researchers due to their promising potentials. In this study, a new nylon 6 electrospun nanofibre incorporated water filtration media prepared by direct electrospinning was studied. The type of filtration media produced using this technique was nanofiltration. Electrospinning technique has been chosen in this study because of its simplicity and low cost. Using this technique, the quality of electrospun nanofibres will highly depend on electrospinning parameters during fabrication process. Therefore, the first objective of this study was to determine the optimum electrospinning parameters, namely electrospinning distance, solution concentration, and applied voltage. The second objective was to evaluate and characterise the filtration media based on results from the first experiment. Triplicate samples were prepared at different deposition times of nanofibre electrospunned to the substrate; 20 s, 40 s, 60 s, 80 s, 100 s and 120 s, to investigate the relationship between the amount of nanofibre and filtration efficiency. The performance of the samples were evaluated based on the filtration test using a vacuum pump in accordance with BS EN 872:2005 Water Quality – Determination of Suspended Solids. Method by Filtration Through Glass Fibre Filters. The water sample was obtained from the new UTeM’s wastewater treatment plant. Suspended solid and chemical oxygen demand (COD) contents were also measured using a colorimeteric method in accordance with Method 8006: HACH Method of Determining Suspended Solid and Method 8000: HACH Method of Determining Chemical Oxygen Demand. The characterisation of the samples was carried out using scanning electron microscopy (SEM) to study the morphological structure of fibres, Energy Dispersive X-Ray Analyzer (EDX) element composition on the filter, ImageJ image analysis to determine average fibre diameter and mercury porosimetry to study porosity of the filters. From the first experiment, the optimum electrospinning distance, solution concentration and applied voltage were found to be at 10 cm, 20 wt.% and 14 kV respectively, based on average fibre diameter, morphological structure of fibres, and deposition amount. The second experiment suggests that the inclusion of electrospun nanofibre had significantly increased the efficiency of the filters. Suspended solid removal has increased to 100% at 80 s deposition time whilst COD has increased to 65% at 120 s deposition time, as compared to control sample (no nanofibre deposition) with 39.3% and 28.8% of suspended solid and COD both at 120 s deposition time, respectively. The effectiveness of the filter was also found to be improved when the amount of nanofibres increased. The inclusion of nanofibre layer provides an effective filtration medium due to their high surface area, small pore sizes and good interconnectivity of the pores. Furthermore, the inclusion of the nanofibres has little effect on the porosity of the developed filters. The knowledge gained from this study could extend the use of electrospun nanofibres in filtration applications. The knowledge would also facilitate new improvements and alternative solutions in any applications that require high surface area and high porosity filtration system.